(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to develop an intelligent model for road maintenance management based on artificial intelligence techniques, within the framework of a desk-based research. The study seeks to analyze the current practices of traditional road maintenance management and identify their shortcomings, particularly in terms of proactive planning and maintenance prioritization. The research adopts a descriptive-analytical approach along with a conceptual design methodology through the review and analysis of relevant literature on infrastructure management and artificial intelligence. The findings indicate that traditional road maintenance management largely relies on reactive interventions after deterioration occurs, leading to increased costs and inefficient use of resources. The study also demonstrates that artificial intelligence represents a modern managerial approach that can effectively support decision-making, enhance planning efficiency, and facilitate the transition toward preventive maintenance. Accordingly, the research proposes a conceptual intelligent model that integrates data, analysis, and decision-making within a comprehensive administrative framework, without addressing technical or implementation aspects. The study concludes that adopting intelligent models in road maintenance management can significantly improve administrative efficiency and contribute to infrastructure sustainability.